2022
DOI: 10.1038/s41417-022-00503-z
|View full text |Cite
|
Sign up to set email alerts
|

CpG-binding protein CFP1 promotes ovarian cancer cell proliferation by regulating BST2 transcription

Abstract: Epigenetic alterations have been functionally linked to ovarian cancer development and occurrence. The CXXC zinc finger protein 1 (CFP1) is an epigenetic regulator involved in DNA methylation and histone modification in mammalian cells. However, its role in ovarian cancer cells is unknown. Here, we show that CFP1 protein is highly expressed in human ovarian cancer tissues. Loss of CFP1 inhibited the growth of human ovarian cancer cells, promoted apoptosis, and increased senescence. CFP1 knockdown resulted in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Bone marrow stromal antigen-2/CD317/Tetherin (BST2), Folate receptor alpha (FOLR1), and Mucin-1 (MUC1) are cell surface proteins previously shown to be overexpressed in ovarian cancer (Gautam et al, 2023; Giampaolino et al, 2020, 2019; Januchowski et al, 2017; Kufe, 2009; Trinidad et al, 2023; Varaganti et al, 2023; Yang et al, 2022). Protein expression of all three biomarkers was demonstrated by western blotting to be present in the EV fractions from human ovarian cancer cell lines (Figure 2) and human plasma (not shown) enriched by size exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Bone marrow stromal antigen-2/CD317/Tetherin (BST2), Folate receptor alpha (FOLR1), and Mucin-1 (MUC1) are cell surface proteins previously shown to be overexpressed in ovarian cancer (Gautam et al, 2023; Giampaolino et al, 2020, 2019; Januchowski et al, 2017; Kufe, 2009; Trinidad et al, 2023; Varaganti et al, 2023; Yang et al, 2022). Protein expression of all three biomarkers was demonstrated by western blotting to be present in the EV fractions from human ovarian cancer cell lines (Figure 2) and human plasma (not shown) enriched by size exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…The CXXC zinc finger protein 1 (CFP1) is an epigenetic regulator involved in DNA methylation and histone modification in mammalian cells. CFP1 promotes ovarian cancer cell proliferation and apoptosis, and the expression of CFP1 is reported to be affected by the CRL4 ubiquitin ligase complex [ 31 ]. Furthermore, cell cycle progression in mammals is modulated by two ubiquitin ligase complexes, CRL4 and SCF, which facilitate the degradation of chromatin substrates involved in the regulation of DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have shown that BST2 upregulation is associated with numerous types of cancer, including endometrial cancer ( 10 ), glioblastoma multiforme ( 12 ), nasopharyngeal cancer ( 14 ), oral cavity cancer ( 15 ), OSCC ( 16 ), cervical cancer ( 17 ), pancreatic cancer ( 19 ), head and neck squamous cell carcinoma ( 23 ), ovarian cancer ( 24 ), esophageal squamous cell carcinoma ( 22 ) and bladder cancer ( 25 ).…”
Section: Bst2: Roles In Carcinogenesismentioning
confidence: 99%
“…Sixth, the transcription factor SP1 protein regulates the BST2 gene by binding to the BST2 promoter, and can promote cell proliferation and migration in pancreatic cancer ( 19 ). The CXXC zinc finger protein 1 can bind to the promoter of BST2 to directly regulate its transcription in ovarian cells ( 24 ). Seventh, the chemokine SDF1a interacts with CXCR4/CXCR7 to promote an invasive phenotype in the medullary thyroid by upregulating BST2 gene expression in thyroid cancer ( 98 ).…”
Section: Bst2: Roles In Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation